(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The study is about the sex difference in job satisfaction and effects of different variables on job satisfaction. A sample of (N=50) medical officers, half males and half females was selected from two government hospitals, one from Faridkot and one from Bathinda. Job Descriptive Index(JDI)( Smith, Kendall, Hulling, 1969) was redesigned according to our cultural values and administered as a measure of respondent’s job satisfaction. Results indicate that factor of sex leads to statistically significant differences in overall job satisfaction of medical officers. Findings supported the hypotheses that male medical officers are more satisfied as compared to female medical officers. Sample appears to be more satisfied with pay, promotion and supervision. Whereas no difference in job satisfaction were found with people and work. Pay, promotion and supervision contribute more toward job satisfaction as compared to people and work.